Legal and Administrative Foundations of Police Activity in Social Order Protection and Public Security - N. Yu. Kolchevskaya; V. S. Vlasova (Сибирское юридическое обозрение)
The article deals with the problems of activities organization of a divisional inspector of police in effectuation of administrative supervision. The authors consider the issues in exposure at administrative stations of the persons who do not comply with administrative restrictions and evade the duties established by administrative supervision as well as preventive measures of corresponding administrative violations of law are considered.